2000
DOI: 10.1128/aem.66.2.700-711.2000
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Dependent and Culture-Independent Characterization of Microbial Assemblages Associated with High-Temperature Petroleum Reservoirs

Abstract: Recent investigations of oil reservoirs in a variety of locales have indicated that these habitats may harbor active thermophilic prokaryotic assemblages. In this study, we used both molecular and culture-based methods to characterize prokaryotic consortia associated with high-temperature, sulfur-rich oil reservoirs in California. Enrichment cultures designed for anaerobic thermophiles, both autotrophic and heterotrophic, were successful at temperatures ranging from 60 to 90°C. Heterotrophic enrichments from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
349
5
7

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 453 publications
(380 citation statements)
references
References 62 publications
19
349
5
7
Order By: Relevance
“…However, several lines of evidence suggest that methanogenic CO 2 reduction, may be more prevalent in petroleum systems. The majority of methanogens identified from oil field waters are CO 2 -reducing methanogens, and acetoclastic methanogens are apparently rare (Magot et al, 2000;Orphan et al, 2000Orphan et al, , 2003Grabowski et al, 2005). Furthermore, experimental measurements of methanogenic pathways in oil field waters also suggest that CO 2 reduction to methane may be more important than acetoclastic methanogenesis in petroleum reservoirs.…”
Section: Thermodynamic Constraints J Dolfing Et Almentioning
confidence: 99%
“…However, several lines of evidence suggest that methanogenic CO 2 reduction, may be more prevalent in petroleum systems. The majority of methanogens identified from oil field waters are CO 2 -reducing methanogens, and acetoclastic methanogens are apparently rare (Magot et al, 2000;Orphan et al, 2000Orphan et al, , 2003Grabowski et al, 2005). Furthermore, experimental measurements of methanogenic pathways in oil field waters also suggest that CO 2 reduction to methane may be more important than acetoclastic methanogenesis in petroleum reservoirs.…”
Section: Thermodynamic Constraints J Dolfing Et Almentioning
confidence: 99%
“…Nonetheless, individual proportions of microbial and thermogenic LMWHC might be generated in different depths prior to mixing. Assuming a geothermal gradient of 0.03°C m − 1 and given that the maximum temperature tolerated by prokaryotes including methanogenic archaea is about 90°C (Orphan et al, 2000;Valentine et al, 2004), microbial methane is formed at burial depths of less than about 2.7 km bsf. In contrast, LMWHC from type II kerogens or oil cracking are typically generated at temperatures exceeding 100°C (Clayton, 1991) implying a minimum formation depth of 3.0 km bsf for the thermogenic LMWHC present in gases from the Batumi seep area.…”
Section: Station Nomentioning
confidence: 99%
“…Recent investigations on an iron-reducing microbial population in the EPR deep-sea hydrothermal vent environment suggested the abundant occurrence of a thermophilic iron-reducing microbial population, predominantly represented by members of Thermococcus and Deferribacter, in relatively oxidative microhabitats (Slobodkin et al, 2001). A body of evidence has demonstrated that sulfidogenic, thermophilic bacteria and archaea, mainly consisting of sulfur-reducing members of Thermotogales and Thermococcales, are predominantly present in global subsurface oil-reservoir environments other than marine hydrothermal systems (L'Haridon et al, 1995;Orphan et al, 2000;Slobodkin et al, 1999;Stetter et al, 1993;Takahata et al, 2000). In addition to members of Thermotogales and Thermococcales, sulfur-reducing and/or metal-reducing members of Deferribacter such as D. desulfuricans SSM1 T and D. thermophilus BMA T may be widely distributed in global deep-sea hydrothermal systems and subsurface oil-reservoir environments and may represent significant microbial components.…”
Section: Comparison With Related Speciesmentioning
confidence: 99%